2016
DOI: 10.1177/0394632016671142
|View full text |Cite
|
Sign up to set email alerts
|

Effects of tranexamic acid on coagulation indexes of patients undergoing heart valve replacement surgery under cardiopulmonary bypass

Abstract: This study aims to explore the effects of tranexamic acid on the coagulation indexes of patients undergoing heart valve replacement surgery under the condition of cardiopulmonary bypass (CPB). One hundred patients who conformed to the inclusive criteria were selected and divided into a tranexamic acid group and a non-tranexamic acid group. They all underwent heart valve replacement surgery under CPB. Patients in the tranexamic acid group were intravenously injected with 1 g of tranexamic acid (100 mL) at the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 16 publications
0
6
1
Order By: Relevance
“…The operative time was also significantly decreased in the treatment group. Intraoperative bleeding increases the operative time because it creates the need for multiple pauses during surgery for suctioning and packing, 28,29 which could explain that result. The previous meta-analysis demonstrated that operative time tended to decrease with the use of tranexamic acid compared to controls but without statistical significance, which was different from our result.…”
Section: Discussionmentioning
confidence: 99%
“…The operative time was also significantly decreased in the treatment group. Intraoperative bleeding increases the operative time because it creates the need for multiple pauses during surgery for suctioning and packing, 28,29 which could explain that result. The previous meta-analysis demonstrated that operative time tended to decrease with the use of tranexamic acid compared to controls but without statistical significance, which was different from our result.…”
Section: Discussionmentioning
confidence: 99%
“…Few studies evaluate the impact of TXA in coagulation parameters. 24 Our results demonstrate a decrease in aPTT when TXA is administered. The latter helps explain the effect of TXA in bleeding control and presents biological plausibility, since TXA is an antifibrinolytic drug.…”
Section: Discussionmentioning
confidence: 48%
“…[43][44][45] Efficacy has been demonstrated in patients undergoing closed-and open-chamber procedures. 5,46 Similarly, aortic procedures involving deep hypothermic circulatory arrest (DHCA), where the effects of hypothermia can further promote fibrinolysis, benefit from TXA. 47,48 However, several questions and concerns remain despite antifibrinolytics becoming a standard of care in this setting.…”
Section: Anesthesia and Analgesiamentioning
confidence: 99%